TINJAUAN TERHADAP SARANA DAN PRASARANA SERTA TATA RUANG PERPUSTAKAAN UNIVERSITAS MUHAMMADIYAH PONTIANAK - Riska, Riska; Amir, Amriani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The purpose of this study was to find out how the facilities and infrastructure as well as the existing layout and conditions of facilities and infrastructure and spatial planning in the Muhammadiyah University Library in Pontianak. The method used by the author in this study is descriptive method with qualitative research methods. Data collection techniques used by the authors in this study are observation, interviews, and documentation. The informants in this study amounted to 2 (two) people who were selected based on predetermined criteria.The results obtained are the facilities and infrastructure available at the Muhammadiyah University Library in Pontianak for now is good enough even though it still has to be added to meet the needs of users. Regarding the condition of facilities and infrastructure in the library such as physical facilities in the form of buildings and equipment and the furniture is good enough. The amount of space in the Pontianak Muhammadiyah University Library is still very minimal because it is constrained by a small building. The processing room which also serves as the librarian's room, the library head's room is sometimes a temporary storage place for newly arrived library materials, a collection room that joins the reading room, a reference collection room, and a circulation room that is only sealed with a table beside the library entrance. Keywords: Facilities, Infrastructure, Spatial Planning, Library